The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1074/jbc.m115.636498
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Platelet-derived Growth Factor Receptor α (PDGFRα) Represses the Production of Oligodendrocytes from Arylsulfatase A-deficient Multipotential Neural Precursor Cells

Abstract: Background: PDGFR␣ is a key signaling component in oligodendrogenesis. Results: Multipotential Neural precursors (NPs) deficient in arylsulfatase A (ASA) show a higher ratio of long versus short fatty acid sulfatides, reduction in PDGFR␣, decreased AKT phosphorylation, and increased exosomal shedding of PDGFR␣. Conclusion: Sulfatides are regulators of NP response to PDGF-AA. Significance: A novel regulatory mechanism of PDGFR␣ signaling is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 100 publications
(90 reference statements)
0
40
0
Order By: Relevance
“…It has been reported that PDGFRα can be secreted through oligodendrocyte‐derived EVs during development . However, the mechanism of PDGFRα release through EVs, and of RTKs in general, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PDGFRα can be secreted through oligodendrocyte‐derived EVs during development . However, the mechanism of PDGFRα release through EVs, and of RTKs in general, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PDGFRa can be secreted through oligodendrocyte-derived EVs during development. (40) However, the mechanism of PDGFRa release through EVs, and of RTKs in general, remains unknown. Some studies demonstrate that association to RalA and RalB proteins (41) or posttranslational modifications such as ISGylation (39) and ubiquitination (32) are essential for general EV secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Akt via adrenal cortical hormones could promote oligodendrogenesis and the effect was abolished by inhibition of Akt (Cai et al 2014; Maki et al 2015). PDGFRα, transferrin and the thrombin receptor also can modulate the generation of OPCs through Akt signaling (Pérez et al 2013; Pituch et al 2015; Yoon et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids such as sulfatides and psychosine, which are accumulated in metachromatic leukodystrophy (MLD) and Krabbe's disease, respectively, and are highly enriched in brain lipid rafts (White et al, ; Moyano et al, ), are good examples of potentially EV‐released neurotoxic lipids. For example, we showed that increased sulfatides in MLD neural precursors parallels the secretion of higher levels of PDGFRα, a key regulator of oligodendroglial proliferation and survival (Pituch et al, ). A direct role for sulfatides in this effect is under investigation (Moyano and Givogri, unpublished), but sulfatides have been found in EVs secreted by mature oligodendrocytes (Kramer‐Albers et al, ).…”
Section: Evs: Shuttling Toxins Within the Nervous System?mentioning
confidence: 99%